Antioxidant and Anticancer Potential of the New Cu(II) Complexes Bearing Imine-Phenolate Ligands with Pendant Amine N-Donor Groups - Adriana Castro Pinheiro; Ianka Jacondino Nunes; Wesley Vieira Ferreira; Paula Pellenz Tomasini; Cristiano Trindade; Carolina Cristóvão Martins; Ethel Antunes Wilhelm; Robson da Silva Oliboni; Paulo Augusto Netz; Rafael Stieler; Osvaldo de Lazaro Casagrande; Jenifer Saffi (MDPI AG, 2023)
Cu(II) complexes bearing NNO-donor Schiff base ligands (2a, b) have been synthesized and characterized. The single crystal X-ray analysis of the 2a complex revealed that a mononuclear and a dinuclear complex co-crystallize in the solid state. The electronic structures of the complexes are optimized by Density Functional Theory (DFT) calculations. The monomeric nature of 2a and 2b species is maintained in solution. Antioxidant activities of the ligands (1a, b) and Cu(II) complexes (2a, b) were determined by in vitro assays such as 1,1-diphenyl-2-picrylhydrazyl free radicals (DPPH.) and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radicals (ABTS+). Our results demonstrated that 2a showed better antioxidant activity. MTT assays were performed to assess the toxicity of ligands and Cu(II) complexes in V79 cells. The antiproliferative activity of compounds was tested against two human tumor cell lines: MCF-7 (breast adenocarcinoma) and SW620 (colorectal carcinoma) and on MRC-5 (normal lung fibroblast). All compounds showed high cytotoxicity in the all-cell lines but showed no selectivity for tumor cell lines. Antiproliferative activity by clonogenic assay 2b showed a more significant inhibitory effect on the MCF-7 cell lines than on MRC-5. DNA damage for the 2b compound at 10 µM concentration was about three times higher in MCF-7 cells than in MRC-5 cells.